From causation to appeal: new functions of the marker pues - Lazo García, Verónica Jenny (2018)
The functions of the discursive marker pues in Spanish spoken in Lima is described in this article. The relationship between the linguistic context with pitch and duration is considered. It is assumed that the discursive functions of the mentioned marker are organized in a semantic continuum of continuity-causality-argumentation-contact-intersubjectivity, which makes it possible to use them in different discourses (narrations, interviews or dialogues). Finally, it is shown how the final position predominates in the spontaneous register (narrative and conversational genres); the initial position, in the semi-spontaneous register (with expressive values of supplication, sarcasm, scolding and reluctance); and the intermediate position, in the semi-formal register (gender interview).